Absence of Susceptibility Vessel Sign in Patients With Malignancy-Related Acute Ischemic Stroke Treated With Mechanical Thrombectomy - Beyeler, Morin; Belachew, Nebiyat F.; Kielkopf, Moritz; Aleman, Enrique B.; León Betancourt, Alejandro Xavier; Genceviciute, Kotryna; Kurmann, Christoph; Grunder, Lorenz; Birner, Barbara; Meinel, Thomas R.; Scutelnic, Adrian; Bücke, Philipp; et al. (Frontiers in Neurology, 2022)
Background and Purpose Clots rich in platelets and fibrin retrieved from patients with acute ischemic stroke (AIS) have been shown to be independently associated with the absence of the susceptibility vessel sign (SVS) on MRI and active malignancy. This study analyzed the association of SVS and the presence of active malignancy in patients with AIS who underwent mechanical thrombectomy (MT). Methods This single-center, retrospective, and cross-sectional study included consecutive patients with AIS with admission MRI treated with MT between January 2010 and December 2018. SVS status was evaluated on susceptibility-weighted imaging. Adjusted odds ratios (aORs) were calculated to determine the association between absent SVS and the presence of active or occult malignancy. The performance of predictive models incorporating and excluding SVS status was compared using areas under the receiver operating characteristics curve (auROC). Results Of 577 patients with AIS with assessable SVS status, 40 (6.9%) had a documented active malignancy and 72 (12.5%) showed no SVS. The absence of SVS was associated with active malignancy (aOR 4.85, 95% CI 1.94–12.11) or occult malignancy (aOR 11.42, 95% CI 2.36–55.20). The auROC of predictive models, including demographics and common malignancy biomarkers, was higher but not significant (0.85 vs. 0.81, p = 0.07) when SVS status was included. Conclusion Absence of SVS on admission MRI of patients with AIS undergoing MT is associated with malignancy, regardless of whether known or occult. Therefore, the SVS might be helpful in detecting paraneoplastic coagulation disorders and occult malignancy in patients with AIS.